Coastal aquaculture ponds represent a notable source of the blooming jellyfish Aurelia coerulea - Wang, Lei; Sun, Tingting; Jiang, Huichao; Zhang, Wenjing; He, Jianlong; Ma, Yuanqing; Zhao, Jianmin; Dong, Zhijun (Frontiers in Ecology and Evolution, 2025)
The frequent occurrence of Aurelia coerulea medusae in coastal waters poses a serious threat to power plants and fisheries, emphasizing the importance of early jellyfish bloom detection. Owing to the complex life cycle of jellyfish and the limitations of traditional survey methods, identifying the natural habitat of early stage jellyfish, especially polyps and ephyrae, is challenging. In this study, we aimed to identify the early habitats A. coerulea using environmental DNA (eDNA) metabarcoding technology to predict the sources of blooms. We successfully detected A. coerulea in a temperate bay (Laizhou Bay, LZB) and nearby aquaculture ponds (Dongying, DY) in March, when medusae were absent, revealing the habitats and distributions of the early stages of bloom-causing jellyfish. The relative abundance of blooming A. coerulea in the DY aquaculture ponds was significantly higher than that in the LZB. Our results suggest that coastal aquaculture ponds, as natural habitats for A. coerulea polyps and ephyrae, are an important source of A. coerulea medusa aggregates in the surrounding coastal waters. These findings suggest that jellyfish management strategies can be focused on aquaculture ponds, allowing for the source-based prevention and control of blooms before they cause damage.